The landslide’s conceptualizing economic decline and its framing effect: Mandarin evidence - Zhang, Yan; Yang, Wenxing (Frontiers in Psychology, 2023)
Conceptual metaphors are essential for explaining and understanding social concerns. Natural disaster metaphors are commonly employed to access the abstract and negative impacts of social issues. Five of the top 10 most prevalent natural disaster frames in the Center for Chinese Linguistics (CCL)—earthquake, flood, fire hazard, drought, typhoon, landslide, volcano, sandstorm, tsunami, and debris flow—share a common economic target domain and show economic recession. Additionally, corpus-based research has revealed that the landslide frame is the most salient in figuratively representing economic declines. An experimental study derived from the corpus analysis has found that the landslide-framed economic crises posed more severity to participants and exerted a notable influence on their opinions and judgments. Therefore, when effective communication of economic hazards is to be realized, metaphorical representation of economic crises demands great consideration.